2014
DOI: 10.5337/2014.208
|View full text |Cite
|
Sign up to set email alerts
|

Land reforms and feminization of agricultural labor in Sughd province, Tajikistan

Abstract: The publications in this series cover a wide range of subjects-from computer modeling to experience with water user associations-and vary in content from directly applicable research to more basic studies, on which applied work ultimately depends. Some research reports are narrowly focused, analytical and detailed empirical studies; others are wide-ranging and synthetic overviews of generic problems.Although most of the reports are published by IWMI staff and their collaborators, we welcome contributions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…One woman relayed that, "until six o'clock the dehqons take water and after six o'clock the people [receive water] but how can women go out at six in the evening and get water?" With male out-migration pervasive in rural areas and an overall feminization of agriculture in Tajikistan, gendered barriers to water access warrant significant consideration [60]. The chairman of the WUA that covers her village said that the timing of water distribution does not present any difficulties for households.…”
Section: "They Do Not Give Any Water To the Village"mentioning
confidence: 99%
“…One woman relayed that, "until six o'clock the dehqons take water and after six o'clock the people [receive water] but how can women go out at six in the evening and get water?" With male out-migration pervasive in rural areas and an overall feminization of agriculture in Tajikistan, gendered barriers to water access warrant significant consideration [60]. The chairman of the WUA that covers her village said that the timing of water distribution does not present any difficulties for households.…”
Section: "They Do Not Give Any Water To the Village"mentioning
confidence: 99%
“…The authors' findings also contrasted regarding the impact of access to irrigation water on farm restructuring. Mukhamedova and Wegerich (2014) found that relative water abundance enhanced farm reform; Nekbakhtshoev (2016) observed that water abundance incited farm chairmen to obstruct farm fragmentation (also observed by Sehring, 2009). Comparing these research findings is however complicated by the fact that these authors' research methods (and related data) differ.…”
Section: Differentiation Within Lowlands and Highlandsmentioning
confidence: 95%
“…However, explaining variations, particularly within districts, is challenging and the precise influence of local geographic characteristics such as population density, water availability and soil fertility on crop diversification and farm restructuring remains difficult to pin down. For instance, whereas Mukhamedova and Wegerich (2014) found that a low land to population ratio obstructed farm reform, Nekbakhtshoev (2016) concluded that localities with a relative labour surplus featured relatively slow processes of farm reform. The authors' findings also contrasted regarding the impact of access to irrigation water on farm restructuring.…”
Section: Differentiation Within Lowlands and Highlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding this, the population is predominantly rural and largely dependent on agriculture, with farmers accounting for 75% of total employment. 36 Poor irrigation has constrained agricultural productivity. While the country has abundant water, management is poor, and much of the infrastructure for both drinking water and irrigation is over 50 years old, resulting in leakage and system failure.…”
Section: Tagoimurod Gulov and Gulnora Kholovamentioning
confidence: 99%